Early Stimulation of the Use Indonesian languange With Interactive Media in Reading Corner Activities in Early Childhood Education - Anjarsari, Irna; Rokhman, Fathur; Pranoto, Yuli Kurniawati Sugiyo (Proceedings of International Conference on Science, Education, and Technology, 2025)
Speaking Indonesian is a literacy skill that is very important to support the success of students in elementary school. This study aims to stimulate children's language maturity before entering elementary school with interactive media in early childhood reading corner activities and provide an overview of good practices for early stimulation of language use in reading corner activities to be interesting with interactive media. This research method uses a type of descriptive qualitative approach by describing phenomena in the field related to student language development with interactive media in reading corner activities. The subjects of this study were 55 students of RPL PG PAUD Universitas Ivet Semarang and 17 children aged 5-6 years at Nurul Wathon Kindergarten, Semarang City. Data collection techniques used closed questionnaires, interviews, observations and documentation of activities. Based on the results of the study on 55 PAUD educator respondents, 85.5% of around 47 people have facilitated and around 14.5% of 8 people have not facilitated reading corner activities. Based on the results of the observation of 5 language assessment criteria from the initial assessment of 17 child respondents, the following category distribution data was obtained: 2 children (11.76%) were classified as "Very Good", 11 children (64.71%) were classified as "Good", and 4 children (23.53%) were classified as "Sufficient". This research contributes to providing an overview of the stimulation of Indonesian development in the combination of vowels and consonants that form words that children enjoy reading with interactive media to the next level of education.